FUNGSI SINTAKSIS FRASA NOMINA DALAM CERKAK “PESUGIHAN KANDHANG BUBRAH” KARYA JMV SUNARDJO PADA RUBRIK ALAMING LELEMBUT MAJALAH PANJEBAR SEMANGAT - Khotimatul Aminah; Khoirul Afidah (Haluan Sastra Budaya, 2022)
Phrases in Javanese are usually composed of two or more words as members. Nominal phrase is a type of phrase that contains the essence of a noun in its constituent elements and can act as a substitute for a noun. Syntax functions related to words or phrases in a sentence consist of subject, predicate, object, complement, description. This study aims to describe the forms and characteristics of the nominal phrase functions contained in the magazine Panjebar Semangat number 52, 26 December 2020 edition. The research method used is descriptive qualitative. The data presented is in the form of a verbal word in the form of a sentence in which there are noun phrases. Sources of data in this study are documents or written data in the form of a softening rubric in Panjebar Semangat magazine number 52 December 26, 2020 edition. Data collection methods in this study are observation and note-taking techniques. The main instrument in this study is the researcher himself (human instrument). The method of data analysis in this research is a separate method using the basic technique for the direct elements (BUL). This study uses triangulation that utilizes theory, namely checking using syntactic theory books. The results of the research are the forms and functions of noun phrases in Panjebar Semangat magazine number 52 December 26, 2020 edition consisting of 3 forms and functions of noun phrases consisting of noun + noun with the findings of the noun phrases bongkotan pring (S) and wooden fork (O), noun + verb, there are findings of my semedic room  that occupy the complement (Pel), noun + adjective, there is a finding that the little one occupies the subject (S).